Ricinus communis: An Efficient Biological Tool for Heavy Metal Removal from Contaminated Soil (Journal of Environmental Bioremediation and Toxicology, 2022)
Heavy metal contamination often occurs when there is an abnormal discharge of metal in the environment. This is caused mainly by human activities such as agriculture, mining and industrialization. When this heavy metal gets into the environment, it adversely affects plants, humans and aquatic biodiversity. Conventional treatment methods have been applied extensively, hence these methods are inefficient and expensive to carry out. This study was conducted to assess whether castor plants could be able to absorb heavy metal actively from the soil. Metal ions determined are lead and copper at different concentrations of 1.5, 2 and 2.5 g/dm3. The soil located at Gombe State University Botanical Garden was used for the cultivation of the plant. Acid digestion and Atomic Absorption Spectroscopy were used for metal determination. The results of the study showed that Copper and Lead were absorbed the highest in the leaves than in stem and root by the absorption efficiency of 100, 91 and 87% respectively. The plant leaves and roots accumulate high Lead content of 2.661, 2.43, in the root, 1.26, 1.52, and 0.031, 0.3 in the stem for both lead and copper respectively. Results of translocation factor revealed the highest absorption of metal from Root to stem of 1.83, 1.98, and the least was 0.36, 0.34, for copper and lead respectively.
Keywords: Heavy metal; Contamination; Castor plant; Translocation factor